The Effect of Metformin on the Proliferation, Apoptosis and CD133 mRNA Expression of Colon Cancer Stem Cells by Upregulation of miR 342-3p - Zhang Y; Chen R; Deng L; Shuai Z; Chen M (Drug Design, Development and Therapy, 2021)
Yaqin Zhang, 1,* Ruofei Chen, 1,* Lili Deng, 2 Zongwen Shuai, 1 Mingwei Chen 2 1Department of Rheumatology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People’s Republic of China; 2Department of Endocrinology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zongwen Shuai; Mingwei Chen Email shuaizongwen@ahmu.edu.cn; chmw1@163.comObjective: To explore whether metformin (MET) can affect the biological behaviour and CD133 mRNA expression of CD133+ colon cancer stem cells (CCSCs) through miR-342-3p.Methods: The direct immunomagnetic bead method was used to select CD133+ CCSCs from the SW480 and HCT116 cell lines, and miRNA-tailing qRT-PCR was used to detect the expression changes of tumor suppressor-related miRNAs (miR-34a, miR-126, miR-143, miR-145, miR-342-3p, miR-342-5p) after MET intervention. Then, miR-342-3p with markedly significant differential expression was selected as the target miRNA. The lentiviruses LV16-hsa-miR-342-3p inhibitor and LV16-NC were used for the transfection inhibition test. CCK-8, flow cytometry, and qRT-PCR were used to detect the cell viability, apoptosis rate, and CD133 mRNA expression of CD133+ CCSCs.Results: Under the high-glucose environment, the expression of tumor suppressor-related miRNAs in CCSCs changed differently (p < 0.05), MET also had different effects on the expression of tumor suppressor-related miRNA under different glucose concentrations (p< 0.05). Among them, MET upregulates the expression of miR-342-3p in CCSCs for the first time. The results of the lentiviruses transfection inhibition test showed that after miR-342-3p was inhibited, the cell viability and apoptosis rate of CD133+ CCSCs did not change significantly compared with before inhibition (p> 0.05), but the expression of CD133 mRNA markedly increased (p< 0.05). Meanwhile, after MET intervention, the apoptosis rate and the expression of CD133 mRNA of CD133+ CCSCs was significantly increased, and the proliferation of CD133+ CCSCs was obviously inhibited (p< 0.05).Conclusion: MET upregulating the expression of miR-342-3p may not have a significant effect on the proliferation and apoptosis of CD133+ CCSCs, but it can reduce the expression of CD133 mRNA in CD133+ CCSCs.Keywords: metformin, colon cancer stem cells, tumor suppressor-related miRNAs, CD133